The New Global Agri-food Order and Water Disputes in Northern Mexico - Quintana S., Victor M. (Universidad del Pacífico, 2013)
The purpose of this article is to show how commercial agriculture processes and climate change are depleting groundwater aquifers in the northern state of Chihuahua, Mexico, as well as to reconstruct the movements, demands and achievements of farmers struggling against the private and exclusionary appropriation of water resources. All of this is linked with the new agri-food global order dominated by finance capital, to speculate with food and biofuel; it is liked also with planetary effects of climate change and their showdown with the ongoing processes of formal recognition.